2022
DOI: 10.3390/met12101677
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Fe-Containing Intermetallic Compounds in Al Alloys: An Overview of Recent Advances from the LiME Research Hub

Abstract: Control of Fe in Al alloys is a severe challenge for the full metal circulation to produce the recycled alloys with mechanical and physical performance as high as the primary alloys. The high restriction of Fe content is mainly due to the deterioration caused by the large-scale Fe-containing intermetallic compounds (FIMCs) in Al alloys. In this paper, recent knowledge gained regarding nucleation, formation, and technical developments on microstructural control and refinement of FIMCs are overviewed. Specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Further observations of the morphology and orientation of cross-sections confirmed that the observed particles corresponded to the metastable β ′′ -Mg 5 Al 2 Si 4 . More specifically a monoclinic unit cell with sides a = 15.16 , b = 4.05 , c = 6.74 , angle β = 105.3 • , and a unit cell volume of V cell = 399.2 3 , characteristic of β ′′ -Mg 5 Al 2 Si 4 was observed as shown in Figure 15c,d. It can be considered as a supercell in the Al matrix with a||<320>Al, b||<001>Al and c||<310>Al.…”
Section: Characterization Of the Aged Materialsmentioning
confidence: 92%
See 1 more Smart Citation
“…Further observations of the morphology and orientation of cross-sections confirmed that the observed particles corresponded to the metastable β ′′ -Mg 5 Al 2 Si 4 . More specifically a monoclinic unit cell with sides a = 15.16 , b = 4.05 , c = 6.74 , angle β = 105.3 • , and a unit cell volume of V cell = 399.2 3 , characteristic of β ′′ -Mg 5 Al 2 Si 4 was observed as shown in Figure 15c,d. It can be considered as a supercell in the Al matrix with a||<320>Al, b||<001>Al and c||<310>Al.…”
Section: Characterization Of the Aged Materialsmentioning
confidence: 92%
“…Coarse Fe-rich intermetallics, eutectics and elemental segregation at grain boundaries and secondary dendrite arms that form upon solidification limit extrudability [1,2]. The β-AlFeSi phase in particular can be very detrimental for extrusion, being prone to nucleating cracks due to its monoclinic structure and plate morphology [3]. Homogenization aims at eliminating the as-cast structure and transforming the β-AlFeSi to α-AlFeSi phase with a cubic structure and globular morphology which is less impactful to extrudability [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated chemical compositions are θ-(Al 76-n Si n )Cu 2 Fe 24 with 4 < n < 6 at 1000 K. Moreover, the configurational entropy contributions further stabi-lize the θ-phase. This information is helpful in investigating the formation of the θ-phase at the phase transformations of the θ-phase to other Fe-IMCs during the casting and related annealing processes of various Al-based alloys [7,52,53].…”
Section: Formation Range and Stability Of θ-(Al 76-n Si N Cu 2 )Fe 24...mentioning
confidence: 99%